DDX50 cooperates with STAU1 to effect stabilization of pro-differentiation RNAs - Weili Miao; Douglas F. Porter; Zurab Siprashvili; Ian D. Ferguson; Luca Ducoli; Duy T. Nguyen; Lisa A. Ko; Vanessa Lopez-Pajares; Suhas Srinivasan; Audrey W. Hong; Yen-Yu Yang; Zhongwen Cao; et al. (Cell Reports)
Summary: Glucose binding can alter protein oligomerization to enable differentiation. Here, we demonstrate that glucose binding is a general capacity of DExD/H-box RNA helicases, including DDX50, which was found to be essential for the differentiation of diverse cell types. Glucose binding to conserved DDX50 ATP binding sequences altered protein conformation and dissociated DDX50 dimers. DDX50 monomers bound STAU1 to redirect STAU1 from an RNA-decay-promoting complex with UPF1 to a DDX50-STAU1 ribonuclear complex. DDX50 and STAU1 bound and stabilized a common set of essential pro-differentiation RNAs, including JUN, OVOL1, CEBPB, PRDM1, and TINCR, whose structures they also modified. These findings uncover a DDX50-mediated mechanism of reprograming STAU1 from its canonical role in Staufen-mediated mRNA decay to an opposite role stabilizing pro-differentiation RNAs and establish an activity for glucose in controlling RNA structure and stability.